IMMUNE STATUS CHARACTERISTICS IN CHILDREN WITH CHRONIC TONSILLITIS ASSOCIATED WITH CYTOMEGALOVIRUS INFECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The elevated incidence of cytomegalovirus (CMV) infection in the pediatric population and its role in sustaining chronic inflammatory processes represent significant challenges in modern pediatrics and otorhinolaryngology. This study presents clinical and laboratory evidence supporting CMV as an important etiological factor in the chronification and recurrent course of tonsillar disease. Given the established capacity of this viral infection to induce autoimmune reactions and modify immune system function, we systematically evaluated the immunological characteristics of chronic tonsillitis in school-aged children with active CMV, with particular focus on cytokine profiles and disturbances in humoral immunity. The results provide a foundation for improving prognostic approaches and designing targeted therapeutic interventions.